PENGARUH VARIASI MATERIAL MATA PAHAT ENDMILL TERHADAP KEKASARAN PERMUKAAN RESIN PADA CNC ROUTER 3018 - Andhika, Muhammad; Ismail, Iskandar; Sani, Almadora Anwar; Tafrant, Dodi (Politeknik Negeri Sriwijaya, Indonesia, 2023)
The purpose of this study is to find out what chisel is the best for cutting acrylic resin and evaluate which one is the best, which can be seen from the surface roughness value obtained through the cutting process. The workpiece materials used in this study are acrylic resins and various types of chisels, namely HSS, carbide and tungsten, Because the chisel has different characteristic properties, so it can be used as a comparison. For the next process, the workpiece is fed three times with a spindle kec of 1000 rpm and a cut kec of 400 mm / minute and a feeding depth of 0.5 mm. It can be concluded that the surface roughness data of the workpiece, the value of the surface roughness of the workpiece of acrylic resin is averaged from the smoothest to the roughest, namely HSS, tungsten chisel, and the roughest carbide. The average roughness value of the HSS chisel is 0.751 Î¼m and the average roughness value of the tungsten chisel is 1.578 Î¼m and the roughness value of the carbide chisel is 1.768 Î¼m.